Direct sunlight driven photocatalytic activity of GeO2/monoclinic-BiVO4 nanoplate composites. (15th May 2017) - Natarajan, Kalithasan; Bajaj, Hari C.; Tayade, Rajesh J.
Graphical abstract: Highlights: GeO2 / monoclinic -BiVO4 photocatalysts were synthesized by hydrothermal method. GeO2 / monoclinic -BiVO4 photocatalysts had substantial visible light absorption. Efficient degradation of RhB dye by 3 wt.% GeO2 / monoclinic -BiVO4 (3-G/ m -B) was achieved under direct sunlight. Improved electron-hole separation due to presence of coupled GeO2 for RhB degradation. The complete degradation of RhB dye was confirmed by HPLC and TOC analysis. Abstract: Visible light active pristine monoclinic -BiVO4 (P/ m -B) and GeO2 / monoclinic -BiVO4 (G/ m -B) nanocomposite photocatalyst with different weight percentages of GeO2 (1, 3 and 5 wt.%) were synthesized by hydrothermal method. The synthesized photocatalytic materials morphology was similar to nanoplate and the light absorption range was in the visible region observed by transmission electron microscopy (TEM) and Ultraviolet–visible Diffuse Reflectance spectroscopy (UV–Vis DRS) analysis. The confirmation of visible light absorption of the photocatalytic materials was demonstrated by performing photocatalytic degradation of rhodamine B (RhB) dye aqueous solution under direct sunlight. Experimental results showed that the enhancement in the photocatalytic activity was more than two times in case of 3 wt.% GeO2 doped BiVO4 (3-G/ m -B) as compared to pristine BiVO4 (P/ m -B). The complete degradation of RhB dye using 3-G/ m -B catalyst was confirmed using high pressure liquid chromatography (HPLC), chemical oxygen demand (COD) and total organic compound (TOC) analysis.